Assessment of aflatoxin exposure, growth faltering and the gut microbiome among children in rural Guatemala: protocol for an observational prospective cohort and bioreactor simulations - Ann C Miller; Qiwen Cheng; Hannah Glesener; Gabriela Montenegro; Olga Torres; Rosa Krajmalnik-Brown; Lee E Voth-Gaeddert (BMJ Publishing Group, 2023)
Introduction Aflatoxin B1 (AFB1) is a carcinogen produced by Aspergillus flavus and Aspergillus parasiticus which grow on maize. Given the high prevalence of child stunting (ie, impaired growth) and other nutritional disorders in low-income and middle-income countries, where maize is consumed, the role of aflatoxin exposure may be significant. Observational reports have demonstrated associations between aflatoxin exposure and impaired child growth; however, most have been cross-sectional and have not assessed seasonal variations in aflatoxin, food preparation and dynamic changes in growth. Biological mechanistic data on how aflatoxin may exert an impact on child growth is missing. This study incorporates a prospective cohort of children from rural Guatemala to assess (1) temporal associations between aflatoxin exposure and child growth and (2) possible mediation of the gut microbiome among aflatoxin exposure, inflammation and child growth.Methods and analysis We will prospectively evaluate aflatoxin exposure and height-for-age difference trajectories for 18 months in a cohort of 185 children aged 6-9 months at enrolment. We will assess aflatoxin exposure levels and biomarkers of gut and systemic inflammation. We will examine the faecal microbiome of each child and identify key species and metabolic pathways for differing AFB1 exposure levels and child growth trajectories. In parallel, we will use bioreactors, inoculated with faeces, to investigate the response of the gut microbiome to varying levels of AFB1 exposure. We will monitor key microbial metabolites and AFB1 biotransformation products to study nutrient metabolism and the impact of the gut microbiome on aflatoxin detoxification/metabolism. Finally, we will use path analysis to summarise the effect of aflatoxin exposure and the gut microbiome on child growth.Ethics and dissemination Ethics approval was obtained from Arizona State University Institutional Review Board (IRB; STUDY00016799) and Wuqu' Kawoq/Maya Health Alliance IRB (WK-2022-003). Findings will be disseminated in scientific presentations and peer-reviewed publications.